REKONSTRUKSI HUKUM BISNIS SYARIAH DALAM MENGHADAPI TRANSFORMASI EKONOMI DIGITAL - Hafidz, Sultan Muhammad; Rusdi Putra, Hikari Fajri; Ramadhan, Fadhlan Tajudin (Taksasila Edukasi Insani, 2025)
The transformation of the digital economy presents new challenges for the Islamic business law system, which is based on the principles of justice, transparency, and blessing. The dynamics of the digital economy, such as e-commerce, fintech, and blockchain, require the reconstruction of Islamic business law to remain relevant and responsive to contemporary developments. This study aims to analyze the necessity of reconstructing Islamic business law in response to the digital economy transformation, using a qualitative approach based on literature review. The findings reveal legal vacuums, a lack of specific regulations, and challenges in integrating Sharia principles into the digital ecosystem. Therefore, regulatory updates, the strengthening of Sharia economic legal literacy on social media, and innovation in digital economic fatwas are needed to build a fair, sustainable, and Sharia-compliant business ecosystem aligned with the maqāṣid al-sharī’ah.Keywords : digital economy, fintech Sharia, Islamic business, legal reconstruction, digital transformation.